Association of cervical artery stenosis with common cerebral microvascular lesions and coronary artery calcifications - Louizi, Chiheb; Khadhraoui, Eya; Lotz, Joachim; Behme, Daniel; Fuchs, Erelle; Kowallick, Johannes T.; Müller, Sebastian J. (Frontiers in Neuroimaging, 2025)
BackgroundA connection between cerebral white matter hyperintensities and coronary artery disease is widely discussed. Both conditions are more prevalent in the elderly. While white matter hyperintensities are often associated with small vessel disease, atherosclerosis is the primary cause of coronary artery disease.MethodsWe evaluated staging CT scans of the body and staging brain MRIs from patients with newly diagnosed malignant melanoma (without metastasis) between 01/01/2015 and 06/30/2023. CT scans were assessed for coronary artery disease using a modified overall visual assessment. Fazekas scores were used to evaluate the MRI for white matter changes. Additional clinical data were obtained from digital patient records.ResultsWe analyzed data from 120 patients (57 females, mean age 68 years, standard deviation 14 years) and found a correlation between coronary artery disease and both age (r = 0.48, α = 0.04) and Fazekas score (periventricular r = 0.46, subcortical and deep white matter r = 0.55). A linear model including age, coronary artery disease, diabetes and arterial hypertension served as a predictor for white matter disease and showed significant correlations. Adding (1) atherosclerosis as well as (2) carotid stenosis to the model resulted in (1) a slight decrease in significance and (2) the unmasking of a potential spurious correlation with carotid stenosis.ConclusionThere is a significant correlation between white matter hyperintensities and both carotid stenoses and coronary artery disease. This finding is clinically relevant: in patients with white matter hyperintensities and coronary artery disease, carotid stenosis should be ruled out.